Understanding Multiple Intelligences for Basic Education (Al-Hasani: Journal of Islamic Studies, 2025)
This article investigates the application and pedagogical implications of Howard Gardner’s theory of multiple intelligences in the context of basic education. Basic education, which encompasses early childhood, primary, and lower secondary levels, serves as the most critical phase in shaping a child's foundational knowledge, skills, attitudes, and values. However, traditional educational systems often rely on narrow academic standards, primarily emphasizing linguistic and logical-mathematical abilities. This approach may overlook the diverse cognitive profiles of students, resulting in disengagement and limited personal development. Gardner’s theory, which identifies ten distinct types of intelligence—linguistic, logical-mathematical, visual-spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, naturalistic, spiritual and existential—offers a broader, more inclusive framework for understanding and nurturing student potential. Through a detailed examination of each intelligence type, this study highlights how basic education can adapt instructional strategies, learning activities, and assessment models to support diverse learners. By aligning curriculum design with multiple intelligences, educators can create dynamic and differentiated learning environments that promote deeper understanding, student engagement, and holistic development. The findings suggest that integrating multiple intelligences into basic education not only improves academic outcomes but also fosters essential life skills such as empathy, creativity, self-reflection, environmental awareness, and collaboration. Ultimately, the theory of multiple intelligences reinforces the need for a child-centered, inclusive, and flexible educational paradigm that respects individual differences and prepares students for the complexities of modern life.